Loving Lactation of Massage Effectiveness to Accelerating Lactation Onset - Utami, Rahayu Budi; Rohuna, Rohuna (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Failure to provide exclusive breastfeeding can be a factor in the occurrence of stunting. The reasons for not giving exclusive breastfeeding, among others, are because the breast milk has not yet come out. Massage is one of the most popular methods among the public. Loving lactation massage has not been widely used. This study aims to analyze the effect of Loving Lactation Massage on postpartum mothers on lactation onset. This type of research is Quasi Experimental with a non-randomized control group design. The population of postpartum mothers in the Perumnas II area of Pontianak City who gave birth to BPM Titin Widyaningsih with the number of samples is 51 people. The sampling technique used was purposive sampling. Data analysis by univariate, bivariate. The hypothesis test used was Anova, with a significance of 95% (Î± = 5%). Results: The average occurrence of lactation onset in the untreated group was 57.17 hours. Conventional group massage 44.17 hours. In the Loving Lactation Massage group, 35.47 hours There was a significant difference between conventional and untreated lactation massage on lactation onset. ((p=0,004). There is a significant difference between the lactation massage with the loving lactation massage method and the untreated lactation onset (p=0,000). Statistically, there was no significant difference between the loving lactation massage method and the conventional method of lactation onset (p=0,079).Â